Particle size-dependent flexibility in DUT-8(Cu) pillared layer metal–organic framework. Issue 9 (8th February 2023) - Maliuta, Mariia; Senkovska, Irena; Thümmler, Ronja; Ehrling, Sebastian; Becker, Sophi; Romaka, Vitaliy; Bon, Volodymyr; Evans, Jack D.; Kaskel, Stefan
Abstract : The nature of metal in the isomorphous flexible DUT-8( M ) ([ M 2 (2, 6-ndc)2 (dabco)] n ) MOFs influences the flexibility, leading to the gate opening behaviour if M = Ni, Co, or Zn and to the breathing if M = Cu. Abstract : The nature of metal in the isomorphous flexible metal–organic frameworks is often reported to influence flexibility and responsivity. A prominent example of such behaviour is the DUT-8( M ) family ([ M 2 (2, 6-ndc)2 (dabco)] n, 2, 6-ndc = 2, 6-naphthalene dicarboxylate, dabco = 1, 4-diazabicyclo-[2.2.2]-octane), where the isostructural compounds with Ni, Zn, Co, and Cu in the paddle wheel cluster are known. The macro-sized crystals of Ni, Co, and Zn based compounds transform to the closed pore (cp) phase under desolvation and show typical gate opening behaviour upon adsorption. The choice of metal, in this case, allows the adjustment of switching kinetics, selectivity in adsorption, and gate-opening pressures. The submicron-sized crystals of of Ni, Co, and Zn based compounds remain in the open pore (op) phase after desolvation. In this contribution, we demonstrate that the presence of Cu in the paddle wheel leads to fundamentally different flexible behaviour. The DUT-8(Cu) desolvation does not lead to the formation of the cp phase, independent of the particle size regime. However, according to in situ powder diffraction analysis, the desolvated, macro-sized crystals of DUT-8(Cu)_op show breathing upon adsorption of CO2 at 195 K. The submicron-sized particles show rigid, nonresponsive behaviour.